Transfer of Land Ownership and Marginalization as Impact of Tourism Industry - Sumarja, Fransiscus Xaverius; Sujadmiko, Bayu; Nguyen, Tien Dung; Rusmawati, Dianne Eka (Faculty of Law, Hasanuddin University, 2023)
Tourism has emerged as one of the foremost industries experiencing rapid growth. Over the past few decades, the sector has witnessed continuous development in Indonesia, evident from the increasing number of foreign tourist arrivals. The rapid growth of tourism in various regions has undeniably yielded positive impacts on both investment and the overall economy. However, it has also given rise to a multitude of challenges that need to be addressed. One of the challenges pertains to the issue of land ownership, specifically concerning the acquisition of residents' lands surrounding tourist destinations by foreign individuals, which is strictly prohibited under Indonesian law. Therefore, a comparative analysis between Indonesia and Malaysia is needed to identify regulation problems to potentially increase cases of legal smuggling of foreign land ownership transfers. This study explains the practice of land ownership by foreigners in the Pesisir Barat District of Lampung, along with the associated problems analyzed through a socio-legal approach. The results show that tourism undeniably benefits the economic sector, and resulted in legal infringements concerning land ownership, leading to the marginalization and displacement of local communities. This study adopts a comparative law method, elucidating the respective provisions of both Indonesia and Malaysia, supplemented by a normative juridical approach to examine legal principles, regulations, and systematics through the examination of relevant library materials.Â Consequently, it is essential to enhance the regulations surrounding the transfer of land to foreigners, including Foreign Citizens and Foreign Legal Entities with representatives in Indonesia, emulating the stringent land tenure restrictions imposed by Malaysia on foreign nationals.